Simultaneous determination of flavor enhancers in stock cube samples by using spectrophotometric data and multivariate calibration - Acebal, Carolina Cecilia (2008)
Spectrophotometric data followed by a suitable treatment of chemometric analysis were used for the simultaneous determination of monosodium glutamate (MSG), guanosine 5′-monophosphate (GMP) and inosine 5′-monophosphate (IMP) in stock cube samples, without any previous extraction step. By this way, the overlapping of the absorption spectra was resolved using a PLS-1 model. The concentration for experimental calibration matrix were varied between 5.03-34.2 μg mL-1 for IMP and GMP, and 448-1399 μg mL-1 for MSG. The relative errors of prediction (REPCV %) were 1.8, 2.8 and 3.1 for IMP, GMP and MSG, respectively. To verify the accuracy of the proposed method a recovery study on real samples was carried out with satisfactory results (92-110%). © 2007 Elsevier Ltd. All rights reserved.